Effect of Amphiphilic Compounds on the Susceptibility of Partially Dehydrated Erythrocytes to Hypertonic Stress - Orlova, N. V.; Shpakova, N. M. (Problems of Cryobiology and Cryomedicine, 2003)
We have studied the effect of various amphiphilic compounds on the susceptibility of partially dehydrated erythrocytes to a hypertonic stress (4.0M NaCl, 37oC). There has been found a high antihaemolytic activity of the representatives of cationic, anionic, nonionic, zwitterionic amphiphilic compounds when removing the cells out of 0.45 and 0.7 M NaCl into the medium, containing 4.0 M NaCl. The values of antihaemolytic activity depended both on the peculiarities of the compounds studied, and on the initial state of cells, subjected to a stress effect.